The Effect of Experiential Learning on Fourth-Grade Students' Learning Outcomes in Integrated Science and Social Studies - Adelia Rizki Ananda; Zulnuraini Zulnuraini; Khairunnisa Khairunnisa; Rizal Rizal; Putriwanti Putriwanti; Surahman Wilade (Journal of Innovation and Research in Primary Education, 2026)
This study examined the effect of the Experiential Learning model on students' learning outcomes in Integrated Science and Social Studies (IPAS) for fourth-grade students at Madrasah Ibtidaiyah Negeri Donggala. The research was motivated by low student engagement and achievement resulting from predominantly teacher-centered instructional practices. A quantitative quasi-experimental design with a nonequivalent control group was employed, involving 48 fourth-grade students divided into experimental and control groups. The experimental group received instruction using the Experiential Learning model emphasizing concrete experience, reflection, conceptualization, and application, while the control group received conventional lecture-based instruction. Data were collected using a validated and reliable 20-item multiple-choice test administered as pretest and posttest. Analysis included descriptive statistics, normality and homogeneity tests, independent samples t-test, and normalized gain (N-gain) calculations. Results revealed a statistically significant difference in posttest scores between groups (t = 9.941, p < 0.001). The experimental group demonstrated substantial improvement with a high mean N-gain score of 0.73, while the control group showed low learning gain (N-gain = 0.21). These findings indicate that Experiential Learning is significantly more effective than conventional teaching methods in improving students' IPAS learning outcomes, supporting its implementation as an instructional approach to enhance student engagement and academic achievement in elementary education.